Evaluation of Myrcia bella in murine osteosarcoma cells: Effect of the extract and enriched fractions of tannins and flavonoids - Fakhoury, Vanessa Svizzero; Pessoa, Adriano de Souza; Tokuhara, Cintia Kazuko; Pagnan, Ana Lígia; Oliveira, Gabriela Silva Neubern de; Liessa, Mariana Rovis Sanches; Inacio, Kelly Karina; Melo, Fernanda Pereira de Souza Rosa de [UNESP]; Dokkedal, Anne Lígia [UNESP]; Oliveira, Rodrigo Cardoso de; Saldanha, Luiz Leonardo [UNESP] (Taylor & Francis, 2021)
Myrcia bella Cambess (Myrtaceae) is an important and common plant, native to the Brazilian Cerrado, with cytotoxicity, antimicrobial, and antidiabetic properties. Therefore, the effects of crude hydroalcoholic extract (CE) and fractions of ellagitannins (ELT) and flavonoids (FV) from Myrcia bella leaves were evaluated in a UMR-106 murine osteosarcoma cells and MC3T3 (normal cell). Cell viability and migration, production of reactive oxygen species (ROS) and matrix metalloproteinase (MMP) −2 and −9 activities were evaluated. In general, CE (80 µg/mL), ELT (160 µg/mL) and FV (64 µg/mL) reduced cell viability (p < 0.05). FV (64 µg/mL) was more effective in inhibition of cell migration, ROS production, and MMP-2 activity when compared to CE and ELT. Myrcia bella a rich source of phenolic compounds and its fraction of flavonoids have cytotoxic effects on osteosarcoma cells, preserving the viability of normal osteoblasts. Due to its antioxidant capacity, flavonoid may be a new therapeutic strategy for cancer.
Keywords: Cell viability; Flavonoids; Medicinal plants; Myrcia bella; Osteosarcoma